2018
DOI: 10.1021/acsaem.7b00164
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Graphene Oxide Supercapacitor Devices

Abstract: The fabrication, characterisation and energy storage capacity of a graphene oxide (GO) based supercapacitor device is reported. This device is fabricated via a facile screen-printing technique, providing a highly reproducible and flexible symmetrical supercapacitor device. The capacitive properties of these GO devices are investigated in both aqueous electrolytes and room temperature ionic liquids. They are shown to improve the capacitive performance from 0.82 F g-1 displayed by a graphitic screen, to 423 Fg-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
71
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(77 citation statements)
references
References 27 publications
0
71
0
1
Order By: Relevance
“…The addition of polymers, namely PPy succeeded in increasing supercapacitor voltage and capacitance compared to carbon which has a smaller voltage and smaller capacitance than GO/PPy (3:10). This is because GO has a large pore with a high surface area wherein the study of Down et al, (2018) GO has a capacitance value of 76 µF in 3M KOH so that the nature of GO supports PPy in maintaining the structure of PPy. The PPy structure has an N group thereby accelerating the transfer of electrons in the GO surface area.…”
Section: Resultsmentioning
confidence: 99%
“…The addition of polymers, namely PPy succeeded in increasing supercapacitor voltage and capacitance compared to carbon which has a smaller voltage and smaller capacitance than GO/PPy (3:10). This is because GO has a large pore with a high surface area wherein the study of Down et al, (2018) GO has a capacitance value of 76 µF in 3M KOH so that the nature of GO supports PPy in maintaining the structure of PPy. The PPy structure has an N group thereby accelerating the transfer of electrons in the GO surface area.…”
Section: Resultsmentioning
confidence: 99%
“…During the combustion, some Ni 2 + may react with carbon and get reduced to Ni metal as per Eq. (2).…”
Section: Crystal Structure and Morphologymentioning
confidence: 99%
“…This can be achieved using oxygen electrode catalyst having porous matrix with hydrophobic and hydrophilic pores. For ORR during discharge, the oxygen must enter through the pores of the catalyst and dissolve in electrolyte then undergo reduction to yield O 2 [2][3][4][5][6] . For this reason, the oxygen electrode should have features of hydrophilic environment having fine pores in contact with electrolyte and hydrophobic gas diffusion layer to facilitate fast transport of oxygen towards the atmosphere/electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…GO contains various oxygenated functional groups such as hydroxyl, epoxy, carbonyl, and carboxyl groups. It has found potential applications in super-capacitors [2][3][4], catalysts [5][6][7], and proton conducting membranes in fuel cell or water electrolysis [8][9][10][11]. It was recently demonstrated that GO shows good proton conductivities that are comparable to that of Nafion.…”
Section: Introductionmentioning
confidence: 99%
“…Nyquist plots of GO membranes at different temperatures. a Pristine GO membrane, b modified GO membrane with 0.01 mmol of Al 3+ and c modified GO membrane with 0.01 mmol of La3 …”
mentioning
confidence: 99%